Analysis and Testing of the Combox Web Application System Using Black Box Testing with the Equivalence Partitioning Method - Dini Nurul Azizah; Ibnu Aqil Mahendar; Muhammad Fillah Alfatih; Setiady Ibrahim Anwar; Nabil Malik Al Hapid; Aditya Wicaksono; Gema Parasti Mindara (International Journal of Electrical Engineering, Mathematics and Computer Science, 2024)
This research focuses on evaluating the Combox web application, a digital tool designed to help Food and Beverage (F&B) business owners strengthen their online presence. The analysis was carried out through Black Box Testing, specifically using the Equivalence Partitioning method, to assess core functionalities like login, logout, product management, and pagination. The findings reveal that while most features function as intended, there are issues with product addition and editing, as well as pagination when no data is available. These results highlight areas that need refinement to improve the application’s reliability and user experience. In summary, this research supports the advancement of a digital platform that enables F&B businesses to harness technology effectively in today’s competitive landscape.